Constraining unintegrated gluon distributions from inclusive photon production in proton-proton collisions at the LHC - Benić, Sanjin; García-Montero, Oscar (Physics letters, 2019)
We compute the leading order (LO) qg→qγ and next-to-leading order (NLO) gg→qq¯γ contributions to inclusive photon production in proton-proton (p+p) collisions at the LHC. These channels provide the dominant contribution at LO and NLO for photon transverse momenta kγ⊥ corresponding to momentum fractions of x≤0.01 in the colliding protons. Our computations, performed in the dilute-dense framework of the Color Glass Condensate effective field theory (CGC EFT), show that the NLO contribution dominates at small-x because it is sensitive to k⊥-dependent unintegrated gluon distributions in both of the protons. We predict a maximal 10% modification of the cross section at low kγ⊥ as a direct consequence of the violation of k⊥-factorization. The coherence effects responsible for this modification are enhanced in nuclei and can be identified from inclusive photon measurements in proton-nucleus collisions. We provide numerical results for the isolated inclusive photon cross section for kγ⊥≤20 GeV in p+p collisions that can be tested in the future at the LHC.